Morphine Decreases Bacterial Phagocytosis by Inhibiting Actin Polymerization through cAMP-, Rac-1-, and p38 MAPK-Dependent Mechanisms - Ninković, Jana (American Society for Investigative Pathology, 2012)
Morphine increases the susceptibility to opportunistic infection by attenuating bacterial clearance through inhibition of Fcγ receptor (FcgR)–mediated phagocytosis. Mechanisms by which morphine inhibits this process remain to be investigated. Actin polymerization is essential for FcgR-mediated internalization; therefore, disruption of the signaling mechanisms involved in this process is detrimental to the phagocytic ability of macrophages. To our knowledge, this study is the first to propose the modulation of actin polymerization and upstream signaling effectors [cAMP, Rac1-GTP, and p38 mitogen-activated protein kinase (MAPK)] as key mechanisms by which morphine leads to inhibition of pathogen clearance. Our results indicate that long-term morphine treatment in vitro and in vivo, through activation of the μ-opioid receptor, leads to an increase in intracellular cAMP, activation of protein kinase A, and inhibition of Rac1-GTPase and p38 MAPK, thereby attenuating actin polymerization and reducing membrane ruffling. Furthermore, because of long-term morphine treatment, FcgR-mediated internalization of opsonized dextran beads is also reduced. Morphine's inhibition of Rac1-GTPase activation is abolished in J774 macrophages transfected with constitutively active pcDNA3-EGFP-Rac1-Q61L plasmid. Dibutyryl-cAMP inhibits, whereas H89 restores, activation of Rac-GTPase and abolishes morphine's inhibitory effect, implicating cAMP as the key effector in morphine's modulation of actin polymerization. These findings indicate that long-term morphine treatment, by increasing intracellular cAMP and activating protein kinase A, leads to inhibition of Rac1-GTPase and p38 MAPK, causing attenuation of actin polymerization, FcgR-mediated phagocytosis, and decreased bacterial clearance.